2008
DOI: 10.1002/jat.1389
|View full text |Cite
|
Sign up to set email alerts
|

Dietary fats altered nephrotoxicity profile of methylmercury in rats

Abstract: Weanling male Sprague-Dawley rats were administered semi-purified isocaloric diet containing soy oil (SO), seal oil (SE), docosahexaenoic acid (DHA), fish oil (FO) or lard (LA) for 28 days, and then gavaged with 0, 1 or 3 mg MeHg kg(-1) body weight per day and fed the same diet for 14 days. Serum and 24 h urine samples were collected on the day of necropsy, and analyzed for markers of kidney function and diseases. Kidney slices were analyzed for para-amino-hippurate (PAH) and tetraethylammonium (TEA) uptake, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 76 publications
2
5
0
Order By: Relevance
“…Interestingly, concomitant treatment with DHA did not change MeHg-induced dyslipidemia. Although the beneficial nutrient of fish oil (DHA) was unable to abolish the deleterious (particularly, dyslipidemic) effects of MeHg, our data do not necessarily contradict the growing body of literature showing the beneficial effects of fish n-3 PUFA against MeHg toxicity (Jin et al, 2009;Kaur et al, 2008). Although the DHA dosage used in our protocol (8 mg/kg) has been shown to display beneficial (anti-inflammatory and renoprotective) effects in mouse models (Kielar et al, 2003) and is near to the recommended intake of DHA + EPA for adult humans (Kris-Etherton et al, 2002), the potential beneficial effects of a higher dose (or longer treatment period) of DHA on MeHg-induced hypercholesterolemia in our experimental model cannot be ruled out.…”
Section: Discussionsupporting
confidence: 52%
“…Interestingly, concomitant treatment with DHA did not change MeHg-induced dyslipidemia. Although the beneficial nutrient of fish oil (DHA) was unable to abolish the deleterious (particularly, dyslipidemic) effects of MeHg, our data do not necessarily contradict the growing body of literature showing the beneficial effects of fish n-3 PUFA against MeHg toxicity (Jin et al, 2009;Kaur et al, 2008). Although the DHA dosage used in our protocol (8 mg/kg) has been shown to display beneficial (anti-inflammatory and renoprotective) effects in mouse models (Kielar et al, 2003) and is near to the recommended intake of DHA + EPA for adult humans (Kris-Etherton et al, 2002), the potential beneficial effects of a higher dose (or longer treatment period) of DHA on MeHg-induced hypercholesterolemia in our experimental model cannot be ruled out.…”
Section: Discussionsupporting
confidence: 52%
“…It is well known that mercury has a nephrotoxic effect [ 7 ] which can occur at low exposure levels [ 8 ]. This toxicity affects primarily the proximal convoluted tubules (PCT) [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, n-3 polyunsaturated fatty acids (PUFA) contained in fish improve brain function (Guesnet et al, 2011;Mourek and Mourek, 2011) and reduce the risk of cardiovascular diseases (Cottin et al, 2011). Some reports indicate that dietary fat can influence oxidative DNA damage, nephrotoxicity, and steroidogenic enzyme activities after MeHg exposure (Grotto et al, 2011;Jin et al, 2008Jin et al, , 2009McVey et al, 2008). However, the human diet varies widely, and some reports have shown that foodstuffs other than seafood may also prevent MeHg toxicity and accumulation (Abdalla et al, 2010;Farina et al, 2005;Lee et al, 1999;Rowland et al, 1986;Sumathi et al, 2012).…”
Section: Introductionmentioning
confidence: 99%